Impact of Photo-Excitation on Leakage Current and Negative Bias Instability in InSnZnO Thickness-Varied Thin-Film Transistors - Dapeng Wang; Mamoru Furuta; Shigekazu Tomai; Koki Yano (Nanomaterials, 2020)
InSnZnO thin-film transistors (ITZO TFTs), having high carrier mobility, guarantee the benefits of potential applications in the next generation of super-high-definition flat-panel displays. However, the impact of photo-excitation on the leakage current and negative bias stress (NBIS) of ITZO TFTs must be further explored. In this study, the ITZO thickness (TITZO) is designed to tailor the initial performance of devices, especially for the 100 nm TITZO TFT, producing excellent electrical properties of 44.26 cm2V−1s−1 mobility, 92 mV/dec. subthreshold swing (SS), 0.04 V hysteresis, and 3.93 × 1010 ON/OFF ratio, which are superior to those of the reported ITZO TFTs. In addition, incident light coupled with tunable photon energy is introduced to monitor the leakage current of various TITZO devices. The OFF-current results demonstrate that under the identical photon energy, many more electrons are photo-excited for the thicker TITZO TFTs. NBIS-induced Vth shift and SS deterioration in all TFTs are traced and analyzed in real time. As the TITZO thickens to near Debye length, the degree of degradation is exacerbated. When the thickness further increases, the notorious instability caused by NBIS is effectively suppressed. This study provides an important research basis for the application of ITZO-based TFTs in future displays.